Perancangan dan Penerapan Instalasi Permanen Air Hujan (IPAH) Sebagai Alternatif Pengelolaan Sumber Daya Air di Desa Jetak, Kecamatan Tulakan, Kabupaten Pacitan, Jawa Timur - Ardhya Nareswari; Muhammad Dhafa Putra Bahagia; Naufal Daffa Herlianto; Bayu Wiranata (Direktorat Pengabdian kepada Masyarakat, 2024)
Groundwater is rainwater that passes through the infiltration process and settles below the soil surface. The ability of soil infiltration begins to decrease due to a poor drainage system and changes in land cover in an area. This causes flooding in big cities and drought during the long dry season. This research was conducted to find out the problem of drought and provide solutions related to this problem. Data analysis was carried out qualitatively to study existing problems and provide solutions to the problems encountered. Based on the research results, it was found that the application of an eco-drainage system is very environmentally friendly and better than conventional drainage. The Rainwater Harvester Installation can be used as a solution to the problem of drought in villages by collecting and filtering the water that will be collected. The level of sustainability of this program is the planning of installations at other points where the authors hope there will be at least one installation from each hamlet.